A Clinical Study for the Influence of Herbal Acupuncture Therapy(Sangsik no.1) on Obesity - Ki-Rok Kwon; Sun-Gu Lee; Young-Shin Kim; Young-Wook Shin; Yun-Yeop Cha (Korean Pharmacopuncture Institute, 2001)
Objectives : The Purpose of this study was to evidence the effect of Herbal Acupuncture therapy(Sangsik no.1) by comparing body fat and obesity degree of Group B(group of Herbal acupuncture therapy and general obesity treatment) with Group A(group of non-Herbal acupuncture therapy and general obesity treatment) in twenty four patients who have received OPD treatment at Sang Ji oriental medical hospital and chiefly diagnosed obesity from June 2000 to September 2001. Methods : We checked the change of Obesity degree with Inbody 3.0. Results and Conclusions : Two groups were no significance, but remarkably showed a significant decrease in Percent Body Fat. According to the above results, it is considered that Herbal Acupuncture therapy(Sangsik no.1) showed a significant decrease in Percent Body Fat, but Others were no significance.